2017
DOI: 10.1007/s00214-017-2082-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and rearrangements of anionic [ClMg(η2-O2C)]− and [ClMg(η2-CO2)]− complexes: a quantum chemical topology study

Abstract: The electronic structure and rearrangements of anionic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…24 It should be strongly emphasized however that such correlation between ELF and chemical bonding is of course just topological, and not energetical. BET has provided meaningful insights on an everincreasing number of reactive processes related to problems in almost all fields of chemistry, 24c, 24d including, for instance, key questions on bonding and reactivity related to the activation of C-H bonds, 25 proton/hydrogen transfer reactions, 26 [4+2] cycloadditions, 9,27 [3+2] cycloadditions, 28 [1,3] dipolar cycloadditions, 9,29 the process of fixation of CO2 by metal complexes, 30 decarbonylation of unsaturated cyclic ketones, 31 the nature of phase transitions for the group IV elements, 32 the formation of hemiaminals, 33 Cope, 9,34 and Claisen 35 rearrangements, the thermal decomposition of -ketoesters, 36 hydrometallation of acetylene, 37 oxidative additions of ammonia to pincer complexes, 38 the Curtis rearrangement, 39 the catalytic Noyori hydrogenation, 40 and the Wittig reaction. 5a In such a context, the suitability of the characterization of the local character of the local ELF function dependents on a proper identification of the associated elementary catastrophes, and hence, the analysis of how the equilibria of ELF change as the control parameters changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 It should be strongly emphasized however that such correlation between ELF and chemical bonding is of course just topological, and not energetical. BET has provided meaningful insights on an everincreasing number of reactive processes related to problems in almost all fields of chemistry, 24c, 24d including, for instance, key questions on bonding and reactivity related to the activation of C-H bonds, 25 proton/hydrogen transfer reactions, 26 [4+2] cycloadditions, 9,27 [3+2] cycloadditions, 28 [1,3] dipolar cycloadditions, 9,29 the process of fixation of CO2 by metal complexes, 30 decarbonylation of unsaturated cyclic ketones, 31 the nature of phase transitions for the group IV elements, 32 the formation of hemiaminals, 33 Cope, 9,34 and Claisen 35 rearrangements, the thermal decomposition of -ketoesters, 36 hydrometallation of acetylene, 37 oxidative additions of ammonia to pincer complexes, 38 the Curtis rearrangement, 39 the catalytic Noyori hydrogenation, 40 and the Wittig reaction. 5a In such a context, the suitability of the characterization of the local character of the local ELF function dependents on a proper identification of the associated elementary catastrophes, and hence, the analysis of how the equilibria of ELF change as the control parameters changes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a description of changes of the topologically defined molecular structures as a response to the variation of control parameters can be addressed via the theory of elementary catastrophes. , It has been mainly exploited within both the QTAIM and ELF ,, frameworks. Within the so-called bonding evolution theory (BET) framework, the transformation of the topology of the ELF along a chosen reaction path (e.g., the intrinsic reaction coordinate (IRC) , ) are characterized in terms of Thom’s elementary catastrophes. ,,, The BET has a demonstrated capability for studying the evolution of the rearrangement of electron pairing (as measured by the ELF) along the reactive path, and hence, chemically significant events, including bond making/breaking processes, become naturally associated with specific structural stability domains (SSDs) separated by catastrophe bifurcations. ,,, BET has provided meaningful insights on an ever-increasing number of reactive processes related to problems in almost all fields of chemistry, , including, for instance, key questions on bonding and reactivity related to the activation of C–H bonds, proton/hydrogen transfer reactions, [4 + 2] cycloadditions, , [3 + 2] cycloadditions, , [1,3] dipolar cycloadditions, ,, the process of fixation of CO 2 by metal complexes, decarbonylation of unsaturated cyclic ketones, the nature of phase transitions for the group IV elements, the formation of hemiaminals, , Cope , and Claisen rearrangements, the thermal decomposition of α-ketoesters, hydrometalation of acetylene, oxidative additions of ammonia to pincer complexes, the Curtis rearrangement, the catalytic Noyori hydrogenation, and the Wittig reaction . We stress that any chemical reaction can, in principle, be in such a way represented in terms of a precise sequence of catastrophic bifurcations associated with electron pairing topologies that enable a straightforward rationalization or interpretation of the evolution of the key chemical concept of bonding patterns. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…39 The B3LYP 40,41 electron density functionals, together with the 6-311+G(d,p) 42 basis set, have been used for all atoms; as in previous studies the use of this methodology has been successfully tested. 6,7,10,11 For each point obtained on the IRC pathway, the topological analysis of the ELF was performed using the TopMod package, 43 considering a cubical grid with a step-size smaller than 0.05 Bohr. The topological partition of the ELF gradient field yields basins of attractors that can be thought of as corresponding to atomic cores, bonds, and lone pairs.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In this sense, previous theoretical studies have been reported and a connection between electron density r(r) distribution and chemical reactivity is found. [1][2][3][4][5][6][7][8][9][10][11][12][13] In addition, developments in ultrafast electron and X-ray diffraction have led to experiments where molecular dynamics can be followed on the time scale of a chemical reaction. [14][15][16] Examples include the seminal work of Zewail on femtosecond dynamics 17 or those based on X-ray diffraction, 18,19 electron diffraction, 20 or laser-induced recollision.…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, our research group published the first study on the molecular mechanism of the 1,3-dipolar cycloaddition by employing BET . Very recently, illustrative examples were presented to show how BET is capable of adequately predicting the bond-breaking/-forming process and the order and direction of the electron density flow of a given chemical rearrangement, thereby providing quite valuable information on the curly arrow representation of the reaction mechanism when studying reaction mechanisms at the elementary level by different authors. ,, …”
Section: Introductionmentioning
confidence: 99%